Endometrial Adenocarcinomas With No Specific Molecular Profile: Morphologic Features and Molecular Alterations of "Copy-number Low" Tumors. (November 2021) - Meljen, Vivienne T.; Mittenzwei, Rhonda; Wong, Janice; Puechl, Allison; Whitaker, Regina; Broadwater, Gloria; Hall, Allison H.; Bean, Sarah M.; Bentley, Rex C.; Elvin, Julia A.; Berchuck, Andrew; Previs, Rebecca A.; et al.
Abstract : The study evaluated morphologic patterns, mutational profiles, and β-catenin immunohistochemistry (IHC) in copy-number low (CNL) endometrial adenocarcinomas (EAs). CNL EAs (n=19) with next-generation or whole genome sequencing results and available tissue for IHC were identified from our institutional database. Clinical data and histologic slides were reviewed. IHC for β-catenin was performed and correlated with mutation status. Images of digital slides of CNL EAs from The Cancer Genome Atlas (TCGA) database (n=90) were blindly reviewed by 4 pathologists, and morphology was correlated with mutation status. Categorical variables were analyzed using the Fisher exact test, and agreement was assessed using Fleiss κ. CTNNB1 mutations were present in 63% (12/19) of CNL EAs. β-catenin nuclear localization was present in 83% of CTNNB1 -mutated tumors (10/12) and in 0% (0/7) of CTNNB1 -wildtype tumors (sensitivity 0.83, specificity 1.00). Squamous differentiation (SD) was present in 47% (9/19) and was more often observed in CTNNB1 -mutated tumors ( P =0.02). Mucinous differentiation (MD) was associated with KRAS mutations ( P <0.01). Digital image review of TCGA CNL EAs revealed that pathologist agreement on SD was strong (κ=0.82), whereas agreement on MD was weak (κ=0.48). Pathologists identified SD in 22% (20/90), which was significantly associated with the presence of CTNNB1 mutations ( P <0.01). CNL EAs demonstrate several morphologies with divergent molecular profiles. SD was significantly associated with CTNNB1 mutations and nuclear localization of β-catenin in these tumors. Nuclear expression of β-catenin is a sensitive and specific IHC marker for CTNNB1 mutations in CNL EAs. CNL EAs with KRAS mutations often displayed MD. Abstract : Supplemental Digital Content is available in the text.